Family Functions in Relation to Behavioral and Psychological Disorders in Chinese Culture. (April 2017) - Fan, Hongying; Zhang, Bingren; Wang, Wei
Family is comprised of two or more individuals related by blood, marriage, or adoption. It basically functions to satisfy the varied hierarchy of needs for each individual. In Chinese culture or society, family structure may have some uniqueness, and its functions are greatly influenced by Confucianism, which suppresses some desires of an individual in order to let him or her fit into the collectivistic community. Contemporary literature has illustrated that many behavioral and psychological disorders in China are associated with family, most of which might be due to the malfunctions of family. There is however no literature that specifically illustrates the link between the Chinese culture and family-related mental disorders. Anxiety, depression, personality disorder, sexual disorder, alcoholism, and others which are documented in China, nevertheless, are related to the malfunctioned family under Chinese culture. Future well-designed studies are needed to fully address the Chinese culture contributions to the etiopathologies of these disorders.